Analyzing Embezzlement in Office in Indonesian Law: Legal Responsibility, Moral Implications, and Recommendations for Reform - Yanto Yanto; Akhmad Suparmin (Jurnal Hukum, 2024)
This research explores the issue of embezzlement in office settings within Indonesian law, particularly focusing on the moral and trust aspects of this crime. The main aim is to analyze the legal responsibility of embezzlers under current Indonesian laws, including the Indonesian Penal Code, and to suggest improvements for future regulations. The study employs a normative research method, examining existing laws through their hierarchy and how they relate to one another. The findings indicate that a perpetrator's intent and mental state are crucial in determining responsibility for embezzlement. The upcoming revisions to the Criminal Code aim to set clear goals for punishment, including preventing future crimes, protecting social norms, and treating convicts humanely. This aligns with Article 372 to Article 376 of the Penal Code, which address theft and embezzlement, emphasizing accountability without degrading human dignity. In conclusion, the research recommends that Indonesian laws regarding embezzlement should include provisions for restitution, encouraging offenders to return stolen funds to the victims. This approach not only promotes accountability but also helps rebuild trust within society. The implications suggest that a balanced legal framework, with punitive measures, could deter future embezzlement and strengthen public confidence in institutions.